Cornering metastases: therapeutic targeting of circulating tumor cells and stem cells - Faltas, Bishoy (Frontiers in Oncology, 2012)
The last decade has witnessed an evolution of our understanding of the biology of the metastatic cascade. Recent insights into the metastatic process show that it is complex, dynamic, and multi-directional. This process starts at a very early stage in the natural history of solid tumor growth leading to early development of metastases that grow in parallel with the primary tumor. The role of stem cells in perpetuating cancer metastases is increasingly becoming more evident. At the same time, there is a growing recognition of the crucial role circulating tumor cells (CTCs) play in the development of metastases. These insights have laid the biological foundations for therapeutic targeting of CTCs, a promising area of research that aims to reduce cancer morbidity and mortality by preventing the development of metastases at a very early stage. The hematogenous transport phase of the metastatic cascade provides critical access to CTCs for therapeutic targeting aiming to interrupt the metastatic process. Recent advances in the fields of nanotechnology and microfluidics have led to the development of several devices for in vivo targeting of CTC during transit in the circulation. Selectin-coated tubes that target cell adhesion molecules, immuno-magnetic separators, and in vivo photo-acoustic flow cytometers are currently being developed for this purpose. On the pharmacological front, several pharmacological and immunological agents targeting cancer stem cells are currently being developed. Such agents may ultimately prove to be effective against circulating tumor stem cells (CTSCs). Although still in its infancy, therapeutic targeting of CTCs and CTSCs offers an unprecedented opportunity to prevent the development of metastasis and potentially alter the natural history of cancer. By rendering cancer a “local” disease, these approaches could lead to major reductions in metastasis-related morbidity and mortality.